Germination and Viability Testing of Some Multipurpose Trees Used in Agroforestry Practices - Puri, Sunil; Agrawal, S.; Patel, R.K.; Swamy, S.L. (Indian Journal of Agroforestry, 2020)
Seed germination and its viability were studied for Acacia nilotica, Bambusa bambos, Leucaena leucocephala, Gmelina arobrea, Albizia pro cera, A. lebbek and Azadirachta indica. In Acacia nilotica soaking of seeds in a cow dung slurry for 24 hrs. recorded a maximum germinability (83.3 %) and also improved the shoot and root lengths. The viability of Bambusa bambos seeds can be enhanced by storage in dessicator. Seeds of Leucaena leucocephala dipped in conc. H2SO4 for 3 min. had a maximum germination of 76.67 per cent. In Gmelina arborea seedling vigour (shoot length, root length, collar diameter, number of leaves) was higher in the plants raised from large size seeds of Pandariya provenance. Albizia lebbek seeds treated with thiourea (0.2 %) had the highest germination per cent (84.3). In seeds stored for 6 months in A. lebbek and Azadirachta indica a rapid decline in moisture - content was observed in later species, while in former species a progressive decline was evident. In neem, the decline of rapid moisture decreased viability. Seedling vigour index was higher in siris as compared to neem. Changes in protein and leachate conductivity of stored neem and siris were also studied. In neem, the proteins declined significantly while conductivity increased in both the species. The results are discussed in relation to storage physiology, ageing and geographical variations.